Correlation between traumatic brain injury, obesity and insulin-resistance – a case report - Laura De Wilde; Charlotte De Ruysscher; Kristine Oostra (Journal of Rehabilitation Medicine - Clinical Communications)
Introduction: Traumatic brain injury is a significant global health concern. It often results from high-velocity accidents and leads to diffuse axonal injury, causing consciousness disorders and potentially permanent cognitive and behavioural changes. Individuals with traumatic brain injury often exhibit weight gain, potentially leading to obesity. This weight increase is influenced by cognitive dysfunction, reduced physical activity and metabolic changes.